Hubungan Masyarakat di Madrasah Ibtidaiyah Negeri (MIN) 2 Kota Malang - Damayanti, Ulfa Dia (Proceedings Series of Educational Studies, 2024)
Abstract The purpose of the research in this article is to find out the management of public relations in madrasas and understand the implementation of public relations management and the constraints that exist in the implementation of public relations management in these madrasas. The research method used in this research is qualitative research, a type of case study with a multi-case design. In the data collection process used data collection techniques with three methods, namely: 1). Observation, 2). Deep interview. The results and discussion in this article are carried out based on previous work programs that have been successful and held again the following year so that after evaluation and holding activities every year to improve education and relations with outside communities in madrasas such as PPDB, insight studies, graduations, work exhibitions students and bazaars, and madrasah birthdays which have been developed so that they are more attractive, with the flagship Insight Studies program. The topic of discussion in this article is to find out how the madrasa flagship program is, why the program is superior, what efforts are being made so that the program can improve the quality of education in the institution Abstrak Tujuan penelitian dalam artikel ini adalah untuk mengetahui manajemen hubungan masyarakat di madrasah dan memahami pelaksanaan manajemen hubungan masyarakat serta kendala yang ada dalam pelaksanaan manajemen hubungan masyarakat di Madrasah tersebut. Metode penelitian yang digunakan dalam penelitian ini yaitu penelitian kualitatif, jenis studi kasus dengan rancangan desain multikasus. Dalam proses pengumpulan data digunakan Teknik pengumpulan data dengan tiga metode yaitu: 1). Observasi, 2). Wawancara mendalam. Pada hasil dan pembahasan dalam artikel ini dilakukan berdasarkan program kerja sebelumnya yang telah berhasil dan diadakan kembali pada tahun berikutnya sehingga setelah adanya evaluasi dan mengadakan kegiatan setiap tahun untuk meningkatkan Pendidikan dan hubungan dengan masyarakat luar di madrasah seperti PPDB, studi wawasan, wisuda, pameran karya siswa dan bazar, dan ulang tahun madrasah yang telah dikembangkan sehingga lebih menarik, engan program unggulan Studi wawasan. Topik pembahasan dalam artikel ini yaitu untuk mengetahui bagaimana program unggulan madrasah, mengapa program tersebut menjadi unggulan, upaya apa yang dilakukan agar program tersebut dapat meningkatkan mutu pendidikan dilembaga tersebut.